Active microstrip log periodic antenna - A. Rahim, Mohamad Kamal (IEEE, 2004)

(untitled)
This paper describes two different configurations of integration active devices into a log periodic antenna (LPA). The first configuration involves the integration of a single amplifier at the input feed line of a five element log periodic antenna (LPA). The second configuration involves the integration of an amplifier in the middle of the five elements LPA. Integrating an amplifier in front of an array introduces signal gain without reducing bandwidth. Integrating an amplifier in the middle of the feed line appears to offer some potential increase in the bandwidth and introduces additional gain for the array, but it also introduces a negative gain slope vs. frequency.